Elaboración de manual de seguridad y salud de trabajo en las unidades de campo de la Carrera de Agrícola ESPAM MFL. - Kuffó Mendoza, Nelly Lisbeth (2015)
The goal of this research was to develop a health and safety manual for the processes developed in the Field Unit of the Agricultural School in the Agricultural Polytechnic School of Manabí Manuel Felix Lopez - ESPAM MFL, which contributed in reducing the risk labor, it could identify the different processes and procedures that are performed in them, the scientific research tools were observation, interviews, records of processes, the methods to implement the activities were bibliographical, documentary analysis, and field research. The information obtained allowed to develop a matrix Iper (Hazard identification en Risk Assessment), then the eminent risks were identified in each of the activities that take effect, being able to fulfill the main goal and provide the safety and health labor manual with their respective alternative of precautions control for employees of the field units, suggestions were made in the manual with evaluative specialized measures.